2013
DOI: 10.1371/journal.pone.0051604
|View full text |Cite
|
Sign up to set email alerts
|

Association between Selected Oral Pathogens and Gastric Precancerous Lesions

Abstract: We examined whether colonization of selected oral pathogens is associated with gastric precancerous lesions in a cross-sectional study. A total of 119 participants were included, of which 37 were cases of chronic atrophic gastritis, intestinal metaplasia, or dysplasia. An oral examination was performed to measure periodontal indices. Plaque and saliva samples were tested with real-time quantitative PCR for DNA levels of pathogens related to periodontal disease (Porphyromonas gingivalis, Tannerella forsythensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 46 publications
(43 reference statements)
2
57
0
Order By: Relevance
“…Individuals with high levels of antibodies against P. gingivalis ATTC 53978 had a two-fold higher risk of pancreatic cancer than individuals with lower levels of anti-P. gingivalis antibodies (Michaud et al, 2012). A year later in a clinical study involving 37 cases of chronic atrophic gastritis, intestinal metaplasia, or dysplasia, DNA levels of periodontopathic bacteria, including P. gingivalis, were measured in plaque and saliva samples by real-time quantitative PCR (Salazar et al, 2013). An elevated but not statistically significant odds ratio for gastric precancerous lesions was observed in relation to increasing colonization with P. gingivalis, Aggregatibacter actinomycetemcomitans and Treponema denticola measured in plaque, and so the study associated high levels of periodontal-pathogen colonization with an increased risk of gastric precancerous lesions in individuals with periodontal disease (Salazar et al, 2013).…”
Section: Historical Perspective and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high levels of antibodies against P. gingivalis ATTC 53978 had a two-fold higher risk of pancreatic cancer than individuals with lower levels of anti-P. gingivalis antibodies (Michaud et al, 2012). A year later in a clinical study involving 37 cases of chronic atrophic gastritis, intestinal metaplasia, or dysplasia, DNA levels of periodontopathic bacteria, including P. gingivalis, were measured in plaque and saliva samples by real-time quantitative PCR (Salazar et al, 2013). An elevated but not statistically significant odds ratio for gastric precancerous lesions was observed in relation to increasing colonization with P. gingivalis, Aggregatibacter actinomycetemcomitans and Treponema denticola measured in plaque, and so the study associated high levels of periodontal-pathogen colonization with an increased risk of gastric precancerous lesions in individuals with periodontal disease (Salazar et al, 2013).…”
Section: Historical Perspective and Clinical Relevancementioning
confidence: 99%
“…A year later in a clinical study involving 37 cases of chronic atrophic gastritis, intestinal metaplasia, or dysplasia, DNA levels of periodontopathic bacteria, including P. gingivalis, were measured in plaque and saliva samples by real-time quantitative PCR (Salazar et al, 2013). An elevated but not statistically significant odds ratio for gastric precancerous lesions was observed in relation to increasing colonization with P. gingivalis, Aggregatibacter actinomycetemcomitans and Treponema denticola measured in plaque, and so the study associated high levels of periodontal-pathogen colonization with an increased risk of gastric precancerous lesions in individuals with periodontal disease (Salazar et al, 2013). A recent case-control study examined the fecal microbiome changes of 19 colorectal cancer patients in comparison to 20 healthy people using 16S rRNA pyro-sequencing .…”
Section: Historical Perspective and Clinical Relevancementioning
confidence: 99%
“…These pathogens could also permeate through diseased periodontal tissues into the systemic circulation to reach distant sites (11). There are numerous scientific reports of periodontal pathogen isolates in various organ systems including lymph nodes (12), arteries (13,14), lung aspirates (9,10), precancerous gastric (15) and colon lesions (16), and esophageal (17) and colorectal cancers (18,19). At the target site, periodontopathogens may promote a permissive microenvironment conducive to cancer progression (8,16,20).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal and CRC pathogens. It has been reported that among patients with periodontal disease, high levels of colonization of periodontal pathogens are associated with an increased risk of gastric precancerous lesions [Salazar et al 2013]. We found the periodontal pathogens F. nucleatum, P. micra and P. stomatis to be commensal but also associated with tumor status and in direct interaction in several data sets.…”
Section: Cohort Specific Speciesmentioning
confidence: 47%